Luciobarbus chelifensis and L. mascarensis, two new species from Algeria (Teleostei: Cyprinidae) - Brahimi, Amina; Freyhof, Jörg; Henrard, Arnaud; Libois, Roland (Zootaxa, 2017)
Cyprinids of the genus Luciobarbus are the most abundant and widespread fishes in most freshwater ecosystems in the Maghreb. In the Mediterranean basin of Morocco, Algeria and Tunisia, all species of Luciobarbus—with exception of L. guercifensis—are superficially very similar and are distinguished mostly by minor morphometric characters. Molecular characters distinguish all species well and nine species are recognised from the area, two of them described here. Luciobarbus chelifensis, from the Chelif River drainage in Algeria, is distinguished by having 41–43+1–2 lateral line scales and a very short anal fin (18–19% SL). Luciobarbus mascarensis, from the Macta River drainage in Algeria, is distinguished by having usually 41+1–2 lateral line scales, a long anal-fin (19–22%) and a short caudal peduncle (15–17% SL). An identification key is given for all African Mediterranean Luciobarbus species except for L. callensis and L. rifensis, which could not be distinguished.